Get More Eyes on Your Work: Visual Approaches for Dissemination and Translation of Education Research. (December 2021) - Rodrigues, Jessica
This article suggests two approaches for sharing education research based on a model of research dissemination for Twitter pioneered by the medical community. The first approach is the visual abstract that reflects a visual summary of a study's textual abstract. Evidence demonstrates that compared with a text-alone approach, the visual abstract yields eight times as many shares on Twitter and three times as many people clicking to access the full article. The second strategy is the translational visual abstract that is designed for sharing education research with nonscientific audiences. I provide a general overview of using Twitter for research dissemination, describe each visual approach and share step-by-step design guidelines, offer recommendations for using these visuals for dissemination purposes, and conclude with future directions for investigating the effectiveness of visual abstracts and translational visual abstracts for communicating education research.